A Real-Time Fall Detection System for Wheelchair Users with Automated Email Alerts - Payarda, Suprabath; Kokkera, Dilip Kumar; Kumar, G. Kranthi; Bodavula, Sanjeev; P, PVRD Prasada Rao (Journal of Neonatal Surgery, 2025)
Goal of Wheelchair Fall Detection System was to enhance safety of wheelchair users. Up to 40 per cent of wheelchair users fall every year and most injuries which result from the falls will be serious and sometimes fatal. To meet this urgent need, we built the WFDS using the latest technology and user centric design to get timely intervention According to our research, existing trustworthy non-intrusive fall detection systems that are geared towards wheelchair users are in short supply. Gyroscopes and accelerometers were used mainly for motion sensors, because of their accuracy in tracking orientation and movement. The Wheelchair Fall Detection System, through the use of machine learning algorithms, detects wheelchair falls at high accuracy, quickly alerts guardians by SMS and email, and greatly increases wheelchair safety.